Gambaran Jumlah Monosit pada Pasien Demam Berdarah Dengue di Rumah Sakit Bhayangkara Kota Kediri - Nita Ermawati; Melisa Aprilia; Mely Purnadianty (Pusat Riset dan Inovasi Nasional, 2024)
Dengue fever is an infectious disease caused by the dengue virus which is carried by the Aedesaegypti and Aedesalbopictus mosquitoes. In DHF patients, thrombocytopenia occurs due to the appearance of antibodies against platelets due to the formation of antigen-antibody complexes. Monocytes are cells capable of fighting infection and responding to dengue-related immunity. This study aims to determine the relationship between Platelet Value and Monocyte Count in Dengue Hemorrhagic Fever Patients at Bhayangkara Hospital, Kediri City. This study used a cross-sectional survey research design. The population of this study is a total of 29 patients. The sample of this study were 26 patients using Accidental Sampling method. The average result of examining the value of Platelets was 64.08 mm³ (64,080 µL) and the number of Monocytes was 15.57%. The results of the examination data were analyzed using Spearman Rank, the value of p = 0.476 (> 0.05) and r = -0.146 means that the correlation level is very low. The conclusion of this study is that there is no correlation between the value of Platelets and the number of Monocytes in Dengue Hemorrhagic Fever Patients at Bhayangkara Hospital, Kediri City.